2007
DOI: 10.1038/sj.emboj.7601562
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution and subunit geometry of human condensin complexes

Abstract: Vertebrate cells possess two different condensin complexes, known as condensin I and condensin II, that play a fundamental role in chromosome assembly and segregation during mitosis. Each complex contains a pair of structural maintenance of chromosomes (SMC) ATPases, a kleisin subunit and two HEAT-repeat subunits. Here we use recombinant human condensin subunits to determine their geometry within each complex. We show that both condensin I and condensin II have a pseudo-symmetrical structure, in which the N-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
110
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(120 citation statements)
references
References 38 publications
(75 reference statements)
10
110
0
Order By: Relevance
“…Silver stain analysis revealed that SMC2-SMC4 heterodimer formation was not affected by any of the mutations, and immunoblotting with CAP-D2 and CAP-H antibodies indicated that the non-SMC subunits of condensin I assembled normally with all of the various mutants. This agrees with in vitro data using baculovirus expressed condensin I (Onn et al, 2007). Thus, a functional condensin ATPase is not a prerequisite for assembly of the complex in vivo.…”
Section: Smc2 Atpase Activity Is Not Required For Formation Of the Cosupporting
confidence: 81%
See 2 more Smart Citations
“…Silver stain analysis revealed that SMC2-SMC4 heterodimer formation was not affected by any of the mutations, and immunoblotting with CAP-D2 and CAP-H antibodies indicated that the non-SMC subunits of condensin I assembled normally with all of the various mutants. This agrees with in vitro data using baculovirus expressed condensin I (Onn et al, 2007). Thus, a functional condensin ATPase is not a prerequisite for assembly of the complex in vivo.…”
Section: Smc2 Atpase Activity Is Not Required For Formation Of the Cosupporting
confidence: 81%
“…Our in vivo studies of condensin function are consistent with recent in vitro studies from the Hirano laboratory, which showed that purified SMC2 undergoes a conformational shift in the presence of ATP, leading to the suggestion that ATP binding might open the hinge region (Onn et al, 2007). Recent studies of cohesin have shown that loading of the complex onto chromatin is caused by transient opening of the hinge domain, and it was hypothesized that this conformational change could be the result of either ATP binding or hydrolysis (Gruber et al, 2006).…”
Section: Mechanistic Differences Between Cohesin and Condensin Atpasesupporting
confidence: 77%
See 1 more Smart Citation
“…Electron microscopic analyses have visualized the highly characteristic architecture of condensin I (Anderson et al 2002), and protein-protein interaction assays using recombinant subunits have revealed the geometry of the subunits within each complex ( Fig. 1A; Onn et al 2007). …”
Section: Eukaryotamentioning
confidence: 99%
“…Potential for elastic behavior of HEAT-repeat molecules is suggested by (i) their solenoidal shapes evocative of a Slinky-like "spring" (14)(15)(16)(17)(18)(19), and (ii) their involvement in reactions involving DNA and membranes, both readily deformable and thus susceptible to an elastic protein/substrate response, e.g., Ataxia telangiectasia and Rad3 related and TOR (15), and cohesin and condensin (e.g., [20][21][22]. Further, TOR responds to plasma membrane deformations (e.g., 23); and the HEAT-repeat protein PR65 is the scaffolding subunit for PP2A, which is directly implicated in responses to spindle tension [e.g., (8); see below].…”
mentioning
confidence: 99%